Temporal changes in fat and protein levels in the tropical Anabantid Trichogaster pectoralis (Regan) - Hails, A. J. (1983)
Samples of a wild population of the Anabantid Trichogaster pectoralis (Regan) were taken during and after one of the two main breeding periods of the year. Carcasses of both sexes and female gonads were analysed for fat, protein and carbohydrate. Carbohydrates were present in insignificant amounts in all tissues. The fat content of the ovary proved to be high (over 30% of wet weight) and, as a result, ovarian energy in a ripe female formed a substantial proportion of the total energy content of the fish. However, it did appear possible for females to develop large ovaries without depleting the carcass fat stores. Although protein levels in the carcass were significantly higher in 1 month, relative to fat levels, protein levels remained fairly constant during the period of study. Conversely fat levels showed marked fluctuations throughout the breeding period, being high at the start of the breeding period, low towards the end, finally rising again 1 month after most fish had terminated breeding. The range of fat levels appeared to be independent of the gonadal state of the fish at capture and seemed more closely related to month of capture. Two explanations are suggested; (1) changes in food availability over the period in question and/or (2) if repeated spawnings occur this could deplete fat reserves in the carcass. In this species fat is stored largely in the muscle but some is stored around the coiled intestine. A visual scoring system was used to assess the extent of this fat deposition and it was found that the fat score was correlated with the level of fat in the carcass. Thus the level of fat around the intestine, although insignificant relative to carcass fat, could be used as a method of assessing the fatness of a fish. Copyright © 1983, Wiley Blackwell. All rights reserved